ENHANCING ENVIRONMENTAL COGNITION BY PRESCHOOLERS THROUGH EXPERIMENTAL ACTIVITIES - Polevikova, Olga; Shvets, Tetiana (Mountain School of Ukrainian Carpaty, 2021)
The paper focuses on the issue of environmental cognition by preschool children via experimental activities. The emphasis is placed on the role of motivation, intellectual games and experiments in children’s perceiving the world. The article presents positive results of the pedagogical experiment (in which participated 83 preschoolers) that proved the effectiveness of the devised methodology. In the article, it is posited that early-age experimentation implies a simple manipulation with things, at which children perform the operations of differentiation, and categorization under various conditions. Specifically, these operations presume simple actions with objects, which vary in color, shape and size. Moreover, preschoolers use different sensory channels to perceive the objects around them. The study maintains that in the junior preschool period children’s cognitive activities are accompanied with role-plays, games, and orientation actions aimed at testing new objects, while senior preschoolers perform similar activities experimenting with objects and employing verbal means like questions why, what for, and how? The study propounds the effective techniques of experimentation with preschoolers, which embrace creating a positive learning environment, employing emotionally colored forms of instruction, maintaining in children a high level of motivation for actions, and using repetitive and suggestive tools. In the course of research, it has been revealed that experimenting is targeted at familiarizing preschool children with specific methods of cognition, measurement tools, and appropriate safety rules, which allow preschoolers to broaden their knowledge and acquire necessary skills in order to be able to create new products independently within specially organized learning activities.